2023
DOI: 10.1021/acsomega.2c06749
|View full text |Cite
|
Sign up to set email alerts
|

Study on Effective Extraction Radius of Directional Long Borehole and Analysis of the Influence Mechanism

Abstract: To accurately determine the effective extraction radius of directional long drilling, the influence of the negative pressure of the hole mouth, the drilling diameter, and the drilling length of the hole on the effective extraction radius of a directional long drilling hole is simulated by establishing a coal-to-gas gas-structure coupling model considering the Klinkenberg effect. Finally, the reliability of the numerical simulation is verified through field testing in Yuxi Coal Mine. The results reveal that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Zhang elucidates the test results of CBM extraction experiments under various borehole deformation instability conditions. It proposes a method for calculating the along-hole resistance coefficient of borehole walls, as follows λ false′ m = 64 ( 1 + 0.04304 italicRe 0.6142 ) , ( Re 2320 ) λ false′ m = false[ 1.14 2 lg ( ε / d + 21.25 italicRe 0.9 ) false] 2 × ( 1 + 0.0163 italicRe 0.2278 ) , ( Re 4000 ) It is necessary to calculate the Reynolds number of the CBM flow in the m-th infinitesimal segment according to the formula below to clarify the flow regime of this segment and determine its along-borehole resistance coefficient Re m = 2 ρ m ( 2 Q m 1 + q m ) μ π d where ρ m is the average density of CBM in the m -th segment, kg/m 3 ; Q m is the original CBM content within the m -th borehole segment, m 3 ; q m is the amount of CBM influx into the borehole wall within the m -th segment, m 3 .…”
Section: Methane-containing Coal Fluid–solid Coupling Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang elucidates the test results of CBM extraction experiments under various borehole deformation instability conditions. It proposes a method for calculating the along-hole resistance coefficient of borehole walls, as follows λ false′ m = 64 ( 1 + 0.04304 italicRe 0.6142 ) , ( Re 2320 ) λ false′ m = false[ 1.14 2 lg ( ε / d + 21.25 italicRe 0.9 ) false] 2 × ( 1 + 0.0163 italicRe 0.2278 ) , ( Re 4000 ) It is necessary to calculate the Reynolds number of the CBM flow in the m-th infinitesimal segment according to the formula below to clarify the flow regime of this segment and determine its along-borehole resistance coefficient Re m = 2 ρ m ( 2 Q m 1 + q m ) μ π d where ρ m is the average density of CBM in the m -th segment, kg/m 3 ; Q m is the original CBM content within the m -th borehole segment, m 3 ; q m is the amount of CBM influx into the borehole wall within the m -th segment, m 3 .…”
Section: Methane-containing Coal Fluid–solid Coupling Modelmentioning
confidence: 99%
“…It proposes a method for calculating the along-hole resistance coefficient of borehole walls, as follows It is necessary to calculate the Reynolds number of the CBM flow in the m-th infinitesimal segment according to the formula below to clarify the flow regime of this segment and determine its along-borehole resistance coefficient. 43 where ρ m is the average density of CBM in the m -th segment, kg/m 3 ; Q m is the original CBM content within the m -th borehole segment, m 3 ; q m is the amount of CBM influx into the borehole wall within the m -th segment, m 3 .…”
Section: Methane-containing Coal Fluid–solid Coupling Modelmentioning
confidence: 99%
“…Although the contact characteristics between surrounding rock and concrete lining are very important, they are rarely considered in most finite element numerical simulation, and few people have studied the change of contact characteristics over time. In the past finite element analysis, the influence of excavation footage and length of excavation step is rarely considered, while the time effect is rarely considered [8] . Therefore, it is necessary to further calculate and discuss the problem of tunnel excavation.…”
Section: Mechanical Analysis Of the Interaction Between Supporting St...mentioning
confidence: 99%
“…With the increase of borehole depth, the friction resistance gradually develops into an exponential relationship. In addition, Liu et al [28] concluded that the effective drainage radius of a directional long drilling hole has an exponential relationship with the distance from the drilling opening. Yuan et al [29,30] conducted the combined drilling method of curtain grouting in underground deep wells, which can significantly reduce the risk of water inrush in deep mining with complex hydrogeological conditions.…”
Section: Introductionmentioning
confidence: 99%